Current knowledge and recent development on management of peripartum cardiomyopathy. Issue 4 (1st June 2017) - Bouabdallaoui, Nadia; Mouquet, Frederic; Lebreton, Guillaume; Demondion, Pierre; Le Jemtel, Thierry H; Ennezat, Pierre V
Abstract: Heart failure with left ventricular dysfunction occurring during pregnancy or during the post-partum period in patients without history of cardiovascular disease defines peripartum cardiomyopathy (PPCM). PPCM carries a high morbidity and mortality rate as well as the possibility of recovery ad integrum. Its incidence shows ethnic variations, with a greater prevalence of the disease among women with African descent. Pathogenesis of PPCM remains poorly understood. Both "oxidative stress–prolactin axis" and "anti-angiogenic-signaling excess" hypotheses are currently being investigated. Novel diagnostic strategies and biomarkers are currently being evaluated. Besides conventional treatment of heart failure, targeted therapies such as pharmacological prolactin blockade are under evaluation. The aim of this short review is to highlight current management as targeted therapy has far been disappointing.